PERAN PSYCHOLOGICAL CAPITAL DAN PERSON – ORGANIZATION FIT TERHADAP KESIAPAN I-GENERATIONS UNTUK BERUBAH - Yanuar Surya Putra (Among Makarti, 2018)
Abstract Organizational change is a major issue affecting all organizations in various industry and government sectors, it can be said that change has become the norm for organizations to maintain the existence and success of the organization. The purpose of this study This study will examine the effect of psychological capital and Person - Organization Fit on individual readiness to change at college graduates in Salatiga who belong to iGeneration group. Generation Z or iGeneration, is a new generation starting their career, so the behavior of this generation in the world of work has not begun to get attention, expectations expected from employees of the Z generation are different from generation Y and generation X. This study uses college graduates in Salatiga as sample, and sampling method used is purposive sampling.  The research instrument used is a questionnaire that was first tested with validity and reliability test. The number of samples used is 170 people. Data analysis was done by Multiple Regression Analysis with equation  path analysis. After the validity and reliability test of the research instrument, the profile of the respondents can be summarized as follows: number of male respondents (63%), age between 21-22 years (74%), duration 1 - 10 months (85%). The results of this study can be summarized as follows: (1) The two variables Psychological Capital and Person - Fit Fit have a positive and significant impact on the desire igenerations to change. (2) Effect of Psychological Capital (31.4%) on the readiness of igenerations to change more high than the influence of Person - Organizations Fit (28.3%). Organizational and managerial support such as effective communication on change, training, coaching and counseling can be regarded as initiatives that can increase individual readiness to change. Employee involvement in the change management process is also believed to enhance meaning and self-confidence and thereby increase individual readiness to change.Keywords: Psychological Capital, Person – Organization Fit, Readiness to Change, iGenerations.